Coverage And Compliance of Mass Drug Administration for Elimination of Lymphatic Filariasis in Endemic Areas of Sagar and Damoh Districts, Madhya Pradesh - Arvind Sharma; P K Kasar (Medsci Publications, 2013)
Background: Lymphatic filariasis (LF) is one of the oldest and most debilitating of the neglected tropical diseases. An estimated 120 million people in 73 endemic countries are currently infected with LF, 53 countries are implementing MDA to interrupt transmission. The mass drug administration (MDA) with single dose of diethylcarbamazine (DEC) was carried out for the eligible population in Sagar and Damoh district of Madhya Pradesh to eliminate LF. Objective: To asses programme in terms of coverage and compliance of MDA against filariasis, reasons for non compliance in Sagar and Damoh district of Madhya Pradesh. Material and Method: A community based cross-sectional survey was conducted in Sagar and Damoh district of MP. A total of eight clusters, one urban and three rural clusters were selected in each district. The data were collected in pretested Performa and analyzed. Results: The study includes 240 families with a total eligible population was 1155 in two districts of eight clusters. The compliance rate were 85.52% in Sagar, 42.82% in Damoh district and total compliance was 66.66% observed by us which was below the expected target .The important cause of non compliance was drug distributor not asked to take drug in front of him 50% and in 23% did not received drug or not present at home at the time of drug distribution. Conclusion: There is urgent need to strengthen MDA programme implementation and effective drug delivery strategies which increase compliance of drug.